Instant city : life and death in karachi - Inskeep, Steve ([S.l.] : Penguin Books, 2012)
Morning Edition cohost Steve Inskeep presents a riveting account of a single harrowing day in December 2009 that sheds light on the constant tensions in Karachi, Pakistan$1 (Bwhen a bomb blast ripped through a Shia religious procession, followed by the torching of hundreds of businesses in Karachi$1 (Bs commercial district. Through interviews with a broad cross section of Karachi residents, Inskeep peels back the layers of that terrible day. It is the beginning, and a constant touchstone, in a journey across the city$1 (Bs epic history and its troubled present Thrilling and deeply researched, Instant City tells the story of one of the world$1 (Bs fastest-growing metropolises and the forces competing to shape its future.s
Keywords: Bombings; Pakistan--Karachi; Social history; Travel; Urbanization